Comparison of Gray Scale and Color Doppler Sonography with Cytopathology Findings in Cervical Lymphadenopathy in Tertiary Level Hospital - Regmi, Dosti; Lohani, Benu; Kayastha, Prakash; Shreevastav, Shreya; Paudel, Sharma; Jha, Sujit Kumar; Bhatta, Uma (Nepalese Journal of Radiology, 2019)
Introduction: Cervical region is the commonest area of lymphadenopathy which is easily accessible to ultrasound and Doppler study. The morphological and vascular-architectural differences among various nodal diseases aids in differentiating benign from malignant causes. Methods: The study was done on the 108 patients referred to Department of Radiology andImaging, TUTH for ultrasound of cervical lymphadenopathy who subsequently underwentFNAC examination. Gray scale evaluation for morphology of the nodes along with Doppler evaluation for resistive index (RI), pulsatility index (PI) and Peak systolic velocity (PSV) were done and correlated with FNAC findings. Results: Among the 108 lymph nodes, 24 were proven to be malignant on FNAC. Features such as S/L ratio >0.5, absence of echogenic hilum, and abnormal vascular pattern demonstrated sensitivities of 96%, 92%, and 87%, specificities of 74%, 65% and 77% and positive predictive values (PPVs) of 51%, 43%, and 55% respectively. The cutoff values for RI, PI and PSV were found to be 0.705, 1.34 and 17.5 cm/s with sensitivities of 96%, 96% and 87%, specificities of 95%, 99% and 88% and positive predictive values (PPVs) of 85%, 95% and 70% respectively. Conclusion: Ultrasound findings of S/L ratio, absence of echogenic hilum, abnormal vascular pattern and Doppler indices revealed good sensitivity, specificity, and accuracy in differentiating benign and malignant lymph nodes.